Natural Multimerization Rules the Performance of Affinity-Based Physical Hydrogels for Stem Cell Encapsulation and Differentiation - Fernandes, Cláudia S. M. (2020)
FCT/MEC (PTDC/BII-BIO/28878/2017; UIDB/04378/2020; UID/QUI/50006/2019; UID/AGR/04129/2019; POCI-01-0145FEDER-007728; LISBOA-01-0145-FEDER-028878); PD/BD/105871/2014; PD/BD/135524/2018;